Divergent Mitochondrial Antioxidant Activities and Lung Alveolar Architecture in the Lungs of Rats and Mice at High Altitude - Jochmans-Lemoine, Alexandra; Revollo, Susana; Villalpando, Gabriella; Valverde, Ibana; Gonzales, Marcelino; Laouafa, Sofien; Soliz, Jorge; Joseph, Vincent (Frontiers in Physiology, 2018)
Compared with mice, adult rats living at 3,600 m above sea level (SL – La Paz, Bolivia) have high hematocrit, signs of pulmonary hypertension, and low lung volume with reduced alveolar surface area. This phenotype is associated with chronic mountain sickness in humans living at high altitude (HA). We tested the hypothesis that this phenotype is associated with impaired gas exchange and oxidative stress in the lungs. We used rats and mice (3 months old) living at HA (La Paz) and SL (Quebec City, Canada) to measure arterial oxygen saturation under graded levels of hypoxia (by pulse oximetry), the alveolar surface area in lung slices and the activity of pro- (NADPH and xanthine oxidases – NOX and XO) and anti- (superoxide dismutase, and glutathione peroxidase – SOD and GPx) oxidant enzymes in cytosolic and mitochondrial lung protein extracts. HA rats have a lower arterial oxygen saturation and reduced alveolar surface area compared to HA mice and SL rats. Enzymatic activities (NOX, XO, SOD, and GPx) in the cytosol were similar between HA and SL animals, but SOD and GPx activities in the mitochondria were 2-3 times higher in HA vs. SL rats, and only marginally higher in HA mice vs. SL mice. Furthermore, the maximum activity of cytochrome oxidase-c (COX) measured in mitochondrial lung extracts was also 2 times higher in HA rats compared with SL rats, while there was only a small increase in HA mice vs. SL mice. Interestingly, compared with SL controls, alterations in lung morphology are not observed for young rats at HA (15 days after birth), and enzymatic activities are only slightly altered. These results suggest that rats living at HA have a gradual reduction of their alveolar surface area beyond the postnatal period. We can speculate that the elevation of SOD, GPx, and COX activities in the lung mitochondria are not sufficient to compensate for oxidative stress, leading to damage of the lung tissue in rats.